Resistencia y tolerancia a oxiuros en cuatro líneas de ratones seleccionados por peso - Orozco, N. (2018)
The ability of the host to reduce the parasite load (resistance) and to limit the damage causedby the pathogen (tolerance) is the result of the co-evolution of the host-guest complex. This is influenced by multiple factors, including the host genotype. In a non selected mice population and in two pairs of lines of divergent selection for body weight for more than 68 generations, infested naturally with Syphacia obvelata and Aspiculuris tetraptera, it was evaluated whether the genotypes of the lines influenced the resistance and tolerance to these parasites. Prevalence and abundance and intensity of the number of eggs per gram of weight were estimated as resistance parameters. The slope of the regression of the weight in the number of eggs was estimated as tolerance parameter. One line selected for high weight showed a significantly lower prevalence than the others (p <0.05); the lines were ordered from the lowest to the highest abundance and intensity of the number of eggs per gram according to body weight. Tolerance estimations were not significant for all lines. The co-evolution of the lines oxyuros led to a differentiation of the acquired resistance but not of the tolerance, in which the genotype of the lines is involved.